Community Forest Program and Women Empowerment: A Study Gorkha District - Gurung, Dil Bahadur (Kaladarpan कलादर्पण, 2024)
Globalization has had a powerful impact on individuals and societies. Some have argued that Nepal entered the age of globalization only in the 1980—after Nepal began to liberalize rules of international trade. Globalization however, also began to impact individuals and societies in Nepal because of the expanding presence of international development agencies there. One such expansion of international agencies was in the community forestry sector. This paper explores how the internationally driven community forestry program in the Gorkha District of Nepal and the associated Community Forest User Group (CFUG) there, is empowering local women. Although forest conservation programs started from 1960s, the initiation of the community forestry program in 1993 helped convert the nationalized forests into community forests that were handed over to local communities. The shift of the ownership and management responsibility of local forests to the local community (CFUG) also shifted the privilege and power to the locals. The initial intent of the program was to protect forest and wildlife and mitigate the hazards caused by deforestation. In time, however, the program was expanded to the holistic development of the community, including the empowerment of women within such community.